2005
DOI: 10.1002/cncr.21289
|View full text |Cite
|
Sign up to set email alerts
|

First analysis of patient demographics, technical reproducibility, cosmesis, and early toxicity

Abstract: BACKGROUNDEighty‐seven institutions participated in a Registry Trial that was designed to collect data on the clinical use of the MammoSite™ breast brachytherapy catheter for delivering breast irradiation. Patient demographics, technical reproducibility, cosmesis, and early toxicity were evaluated.METHODSFrom May 4, 2002 through July 30, 2004, 1419 patients with Stage 0, I, or II breast carcinoma who were undergoing breast‐conserving therapy were enrolled on the trial. The device was placed in 1403 of these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(26 citation statements)
references
References 29 publications
2
23
1
Order By: Relevance
“…The patients were eligible for the study on the basis of the unicentric nature of the ipsilateral recurrence that could be removed at the time of lumpectomy achieving negative margins. The tumor size and histology characteristics of the second breast cancer events treated on our study using multicatheter interstitial PBB are very similar to the new primary breast cancers (median tumor size of 1.0 cm, and included 86% invasive cancer and 14% DCIS lesions) that were treated with Mammosite catheter brachytherapy (41).…”
Section: Discussionmentioning
confidence: 97%
“…The patients were eligible for the study on the basis of the unicentric nature of the ipsilateral recurrence that could be removed at the time of lumpectomy achieving negative margins. The tumor size and histology characteristics of the second breast cancer events treated on our study using multicatheter interstitial PBB are very similar to the new primary breast cancers (median tumor size of 1.0 cm, and included 86% invasive cancer and 14% DCIS lesions) that were treated with Mammosite catheter brachytherapy (41).…”
Section: Discussionmentioning
confidence: 97%
“…Preliminary results from clinical trials indicate that breast conserving surgery in conjunction with balloon brachytherapy can lead to good cosmetic outcomes, comparable to the interstitial approach. [4][5][6][7][8] At the present, balloon brachytherapy is conventionally delivered with a HDR 192 Ir source, but it can also be delivered with an electronic brachytherapy ͑eBx͒ source involving a miniaturized x-ray tube. [9][10][11][12] Ir radionuclide emits several gamma rays with energies up to 1.4 MeV that can easily penetrate through a large portion of the patient's body.…”
mentioning
confidence: 99%
“…On the contrary, Reitsamer [15], in a non-randomized study, showed that the boost given with intra-operative electron radiotherapy is superior to the external breast electron boost irradiation. Partial breast irradiation can be delivered also with interstitial brachytherapy [16][17][18], and more recently by external sources with three-dimensional radiotherapy (3D-RT) and intensity modulated radiotherapy (IMRT) [19][20].…”
Section: Discussionmentioning
confidence: 99%